Development Of Digital Book Stem With Design Thinking Assisted By Augmented Reality In Improving Mathematical Literacy Abilities - Lutfiyana Lutfiyana; FX Didik Purwosetiyono; Muhtarom Muhtarom (Universitas Wiralodra, 2025)
This study aims to develop digital book learning media based on STEM with a Design Thinking approach and assisted by Augmented Reality (AR) to improve students' mathematical literacy skills. Media development was carried out using the ASSURE model consisting of six stages: (1) Analyze Learners, analyzing the characteristics of class VIII students of MTsN 3 Grobogan; (2) State Objectives, formulating learning objectives that integrate mathematical literacy and the STEM approach; (3) Select Methods, Media, and Materials, choosing PJBL strategies, AR technology, and curriculum-based materials; (4) Utilize Media and Materials, developing and implementing interactive digital books in learning; (5) Require Learner Participation, encouraging active student involvement through project completion and exploration of AR features; and (6) Evaluate and Revise, conducting trials, evaluating media effectiveness, and revisions based on student and validator input. The subjects of the study were class VIII students of MTsN 3 Grobogan. Data collection was carried out through pretest-posttest, student response questionnaires, and expert validation. The trial results show that this interactive digital book media is effective in improving students' mathematical literacy skills, interesting to use, and encourages students' active involvement in project-based and technology-based learning. Thus, this media is worthy of being used as an innovative alternative in mathematics learning.